Calcium channel subtypes contributing to acetylcholine release from normal, 4-aminopyridine-treated and myasthenic syndrome auto-antibodies-affected neuromuscular junctions. - Giovannini, F; Sher, E; Webster, R; Boot, J; Lang, B (2002)
1 Acetylcholine release at the neuromuscular junction relies on rapid, local and transient calcium increase at presynaptic active zones, triggered by the ion influx through voltage-dependent calcium channels (VDCCs) clustered on the presynaptic membrane. Pharmacological investigation of the role of different VDCC subtypes (L-, N-, P/Q- and R-type) in spontaneous and evoked acetylcholine (ACh) release was carried out in adult mouse neuromuscular junctions (NMJs) under normal and pathological conditions. 2 omega-Agatoxin IVA (500 nM), a specific P/Q-type VDCC blocker, abolished end plate potentials (EPPs) in normal NMJs. However, when neurotransmitter release was potentiated by the presence of the K(+) channel blocker 4-aminopyridine (4-AP), an omega-agatoxin IVA- and omega-conotoxin MVIIC-resistant component was detected. This resistant component was only partially sensitive to 1 micro M omega-conotoxin GVIA (N-type VDCC blocker), but insensitive to any other known VDCC blockers. Spontaneous release was dependent only on P/Q-type VDCC in normal NMJs. However, in the presence of 4-AP, it relied on L-type VDCCs too. 3 ACh release from normal NMJs was compared with that of NMJs of mice passively injected with IgGs obtained from patients with Lambert-Eaton myasthenic syndrome (LEMS), a disorder characterized by a compromised neurotransmitter release. Differently from normal NMJs, in LEMS IgGs-treated NMJs an omega-agatoxin IVA-resistant EPP component was detected, which was only partially blocked by calciseptine (1 micro M), a specific L-type VDCC blocker. 4 Altogether, these data demonstrate that multiple VDCC subtypes are present at the mouse NMJ and that a resistant component can be identified under 'pharmacological' and/or 'pathological' conditions.